Critical Factors That Influence The Effectiveness Of CSR Initiatives In Malaysia Manufacturing Industries - Wong, Kit Yang (2009)
This study investigated how organizations in Malaysia were involved in corporate social responsibility and further explored the methods and incentives that could bring positive results to corporate social responsibility. Data was collected via a survey questionaire.